2017
DOI: 10.17221/210/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of Juniperus communis L. essential oil in cooked pork sausages

Abstract: The antioxidant and antimicrobial activity of Juniperus communis L. essential oil (JO) in cooked sausages was examined. Sausages with different concentrations of JO (0.15.0 µl/g) and a control were prepared. Instrumental parameters of colour (CIE L*a*b*), TBARS values, DPPH scavenging activity assay, microbial profile, and sensory panel scores have been assessed. Batches produced with the JO addition were darker and redder compared to the control. Sausages with the addition of 1.0, 2.0 and 5.0 µl/g JO showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…Moreover, storage time had the effect of decreasing L* values, according with the findings of Pateiro et al [55]. Finally, the addition of JEO decreased the L* value, probably as the result of interactions among bioactive compounds of JEO (phenolics, terpenes) and myoglobin [30]. The two-way (FC × SD) and four-way (FC × NC × SD × JC) interactions were also significant (p < 0.05) for L* values (Table S2).…”
Section: Ph and Instrumental Parameters Of Color Of Dry Fermented Sausupporting
confidence: 63%
See 3 more Smart Citations
“…Moreover, storage time had the effect of decreasing L* values, according with the findings of Pateiro et al [55]. Finally, the addition of JEO decreased the L* value, probably as the result of interactions among bioactive compounds of JEO (phenolics, terpenes) and myoglobin [30]. The two-way (FC × SD) and four-way (FC × NC × SD × JC) interactions were also significant (p < 0.05) for L* values (Table S2).…”
Section: Ph and Instrumental Parameters Of Color Of Dry Fermented Sausupporting
confidence: 63%
“…However, in an earlier study, Schelz et al [28] determined the strong antimicrobial potential of Juniperus communis L. essential oil against Saccharomyces cerevisiae. In our previous research, we found that Juniperus communis L. essential oil efficiently suppressed lipid oxidation and microbial growth and enhanced the color of cooked pork sausages [30].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Currently, coniferous shoots are almost absent as a food ingredient despite their wide availability in many parts of the world. The exceptions are the common juniper, whose berry-like cones are a spice valued in Europe and pine shoots [2]. Products with pine shoots are available on the market, including pine shoot syrup, beer made with pine shoots or herbal teas.…”
Section: Introductionmentioning
confidence: 99%